Hubungan Kecerdasan Emosional Dan Hasil Belajar Dengan Kualitas Komunikasi Mahasiswa Fakultas Ekonomi - Darmawan, Didit; Mardikaningsih, Rahayu (Forum Kerjasama Pendidikan Tinggi, 2022)
Communication is very essential in human life. Communication as a social interaction tool is useful for knowing and predicting other people's attitudes, as well as for knowing one's own existence in creating a balance with society or the environment. Interpersonal communication is a communication skill since childhood, from the closest environment. Experts have identified various approaches to studying the quality of communication. Emotions and intellectual intelligence can be a factor in developing the quality of communication. In addition, learning outcomes can be used as a reason for the formation of quality communication. This study aims to determine the role of emotional intelligence and learning outcomes on the quality of interpersonal communication between students and lecturers at UNSURI Surabaya. The population in this study were all students at the Faculty of Economics. Sampling using purposive sampling method. The number of samples is 128 people. Data collection uses a survey method. The data analysis technique used in this study is a multiple regression technique to determine the effect of the independent variables on the dependent variable. The results prove that there is a role of emotional intelligence and learning outcomes on the quality of communication between lecturers and students.